The Influence of Transformational Leadership And Innovation on Performance of Bulog Aceh Regional Office with Organizational Culture and Intellectual Capital as Mediator (International Journal of Scientific Research and Management (IJSRM), 2025)
This research aims to examine the impact of transformational leadership and innovation on the performance of the Bulog Aceh Regional Office (Bulog Aceh), with organizational culture and intellectual capital serving as mediators. The study population consists of all employees of Bulog Aceh, totaling 117 individuals. The sample size was determined using a census method, which involves utilizing the entire population as the sample. The analysis method employed is Partial Least Squares (PLS). The result shows that transformational leadership and innovation affect organizational culture, intellectual capital, and organizational performance; organizational culture and intellectual capital affect organizational performance, and; organizational culture and intellectual capital mediate transformational leadership and innovation affect organizational performance. These findings explain that the model for increasing organizational performance is a function of strengthening transformational leadership and innovation, conformity to organizational culture, and increasing intellectual capital.